The Effect of Applying The Talk-to-The Text Strategy on Students' Reading COmprehension in Narrative Text - Fadhila Yonata (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2018)
This study investigates the effect of applying the talk-to-the-text strategy on students’ reading comprehension of narrative text. By employing quasi-experimental research design, specifically pre- and post-tests design one, talk-to-the-text reading strategy was implemented as treatment in experimental class and another control class was taught by utilizing conventional strategy. The study was conducted in the eighth grade students of Junior Secondary School in one of school in Bintan, Indonesia. Cluster random sampling was employed in order to determine the samples. In gaining the data, the instrument used was reading comprehension test. Based on data analysis by using t-test, the result revealed that talk-to-the-text strategy give better effect toward comprehension of grade eight students when reading narrative texts.